2011
DOI: 10.1007/s10535-011-0114-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of peroxisomes in the oxidative injury induced by 2,4-dichlorophenoxyacetic acid in leaves of pea plants

Abstract: The role of peroxisomes in the oxidative injury induced by the auxin herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) in leaves of pea (Pisum sativum L.) plants was studied. Applications of (2,4-D) on leaves or to root substrate increased the superoxide radical production in leaf peroxisomes. Foliar application also increased H 2 O 2 contents in leaf peroxisomes. Reactive oxygen species (ROS) overproduction was accompanied by oxidative stress, as shown by the changes in lipid peroxidation, protein carbonyls,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Previously, the peroxisomal enzyme XOD (Sandalio et al 1988) was demonstrated to be involved in ROS production induced by 2,4-D (Romero-Puertas et al 2004a;McCarthy-Su arez et al 2011;Pazmiño et al 2011). Analysis of XOD activity with native PAGE and spectrophotometry showed an increase in XOD activity with 2,4-D and a change in mobility of the protein in pea leaves treated with 2,4-D (Fig.…”
Section: Regulation Of Ros Production and Ethylene Emission By 24-dmentioning
confidence: 87%
See 2 more Smart Citations
“…Previously, the peroxisomal enzyme XOD (Sandalio et al 1988) was demonstrated to be involved in ROS production induced by 2,4-D (Romero-Puertas et al 2004a;McCarthy-Su arez et al 2011;Pazmiño et al 2011). Analysis of XOD activity with native PAGE and spectrophotometry showed an increase in XOD activity with 2,4-D and a change in mobility of the protein in pea leaves treated with 2,4-D (Fig.…”
Section: Regulation Of Ros Production and Ethylene Emission By 24-dmentioning
confidence: 87%
“…In animal tissue, it has been demonstrated that XOD can be phosphorylated (Kayyali et al 2001), although the effect of this modification on XOD activity has not been studied. Recently, we detected an increase in this activity in pea plants exposed to different concentrations of 2,4-D (McCarthy-Su arez et al 2011;Pazmiño et al 2011). Acyl CoA oxidase (ACX) from the fatty acid b-oxidation pathway is also stimulated in response to 2,4-D treatment (McCarthy-Su arez et al 2011;Pazmiño et al 2011) and could also contribute to ROS production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pea plants exposed to 2,4‐D also develop oxidative stress symptoms characterized by H 2 O 2 over‐accumulation, lipid peroxidation, protein oxidation and induction of proteolysis (McCarthy 2004; Romero‐Puertas et al . 2004a; McCarthy‐Suárez et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the cells of higher plants, NADP-ICDH activity has been detected and characterized in the different subcellular compartments including the cytosol, mitochondria, chloroplasts and peroxisomes (Attucci et al 1994, Rasmusson and Møller 1998, Corpas et al 1999b, Leterrier et al 2007, Pascual et al 2008, McCarthy-Suárez et al 2011). Significant progress is being achieved in understanding how the NADP-ICDH is involved in nitrogen metabolism, in redox regulation, and in response to oxidative stress (Scheible et al 2000, Hodges et al 2003, Valderrama et al 2006, Mateos et al 2009, Mhamdi et al 2010, Sulpice et al 2010.…”
Section: Introductionmentioning
confidence: 99%